Realistic Mathematics Education (RME) Approach to Material on the Characteristics of Two-Dimentional Figures Using the Reog Ponorogo Performance in Elementary Schools - Wiryanto, Wiryanto; Rahmawati, Ika; Humaira, Firda (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
:   It is critical to approach mathematical education correctly. This is because many students believe math is a tough subject to learn. This problem arises because many teachers teach mathematics in abstract terms. This is a qualitative descriptive study using Graveimeiijeir's design research method. The research was designed to prove the truth of the allegations made in the learning trajectory or HLT (Hypothetical Learning Trajectory) and their impact on students' understanding by applying the RME (Realistic Mathematics Education) approach to the material on the characteristics of two-dimensional figures, with Reog Ponorogo performance media and worksheet serving as a guide for student activities. This study was conducted on class 3B students at MI Ma'arif Darul Ulum Pondok. The research topic is a 6-student group in a classroom. The research stages included preparation, execution in the classroom, and data analysis. Based on this research, it can be seen that the stages of learning activities using the RME approach are based on the stages contained in the iceberg theory, namely, stages of real-world situations (situations), models that describe problem situations (model of), models for solving problems (model for), and formal mathematics stages using Reog Ponorogo performance media can make it easier for students to understand material regarding the characteristics of two-dimensional figures.